Pengaruh Environmental, Social, and Governance (ESG) terhadap Price to Book Value (PBV) Saham PT Energi Mega Persada pada Periode 2022–2024 - Agung Budi Darmoyo; Vera Salma Meilana; Ovalia Ovalia (Journal of Innovative and Creativity, 2026)
This study investigates the influence of Environmental, Social, and Governance (ESG) performance on the Price-to-Book Value (PBV) of PT Energi Mega Persada Tbk (EMP) during the 2022–2024 period, a time marked by global energy volatility and increasing sustainability disclosure requirements. The purpose of the study was to examine whether improvements in ESG disclosures within Annual Reports and Sustainability Reports translate into higher market valuation, particularly in the energy sector, which faces significant environmental and social scrutiny. The research builds upon the stakeholder theory, legitimacy theory, and agency theory to understand the mechanisms through which ESG may affect firm value. Materials and methods. The study employed a quantitative explanatory research design, using secondary data extracted from EMP’s sustainability disclosures and financial statements. ESG was measured using a disclosure index based on environmental, social, and governance indicators identified through content analysis and validated using NVivo for systematic coding reliability. PBV was computed using market price and book value per share, while firm size and profitability were included as control variables. Regression models—simple and multiple linear—were applied to test the effect of ESG (overall and by dimension) on PBV after passing classical assumption tests. Results. The findings indicate that overall ESG disclosure exhibits a positive but varying degree of influence on PBV. The environmental dimension contributed through emission reduction initiatives and waste management improvements, while the social dimension demonstrated strong consistency through zero fatality rates and increased CSR investment. Governance improvements, such as the establishment of an ESG Committee and UNGC membership, reinforced institutional credibility. PBV remained relatively stable throughout the observed period, reflecting steady investor confidence. Conclusions. The study concludes that ESG plays a relevant role in shaping market perception and valuation of energy companies in Indonesia. Improved sustainability performance enhances operational credibility and supports stable PBV trends despite market fluctuations. These findings highlight the importance of ESG integration as a strategic driver of long-term corporate value, particularly in environmentally sensitive industries.